Anti-Asian Hatred and Japanese Parents' Support of Their Children's Acculturation to the United States. Issue 4 (23rd July 2022) - Kayama, Misa; Haight, Wendy
Abstract: This ethnographic study explores how Japanese immigrant and temporary resident parents support their children's acculturation to U.S. society. Anti-Asian hatred is a neglected social justice issue with a long history extending to hate crimes during the COVID-19 pandemic. Yet the U.S. population includes an increasing number of Asian immigrants. Some of them, such as recent Japanese immigrants and temporary residents, are from majority groups in their countries of origin, and do not have cultural socialization practices to protect their children from racism and xenophobia. This article focuses on in-depth, individual interviews with 14 Japanese immigrant and temporary resident parents of children attending U.S. local schools. Parents described their cultural socialization as centering on developing a Japanese cultural self, for example, through participation in a Japanese supplementary school. Parents also reported experiences of anti-Asian racism and xenophobia, including social exclusion. However, they typically did not describe preparing children directly for responding to and coping with anti-Asian bias. Rather, they and their children took responsibility for bias directed against them, and avoided drawing attention to their differences. Authors discuss implications for how social workers can recognize distress in Japanese children and effectively support them and others experiencing similar acculturation challenges.